A questão do libro didático de ensino de uma língua estrangeira e o papel do professor antes de adotá-lo - de Meneses Mitma, Simone (2022)
The didactic book represents one of the main working tools for the teacher throughout the teaching and learning process. However, in view of the growing number of researches on this material, it is observed that there are a series of problems that involve not only aspects related to its content, but also to how it is being received in the institutions. The main objective of this article is to highlight some questions that surround textbooks for teaching a foreign language (FL) from bibliographical research on works that have been based on the analysis of FL textbooks. In addition, this article discusses the role of the teacher before adopting it. The points of view of Coracini (2021) and Taset (2015) contribute to clarify some points on this topic. It is recognized the importance of the teacher's training to be able to adapt the didactic book according to its context of use and to know the main needs of the learners in relation to the language they intend to study.